'It was me answering my own questions': Experiences of method of levels therapy amongst people with first‐episode psychosis. (31st January 2019) - Griffiths, Robert; Mansell, Warren; Edge, Dawn; Carey, Timothy A.; Peel, Heather; J. Tai, Sara
Abstract: In this study, we aimed to understand how people with first‐episode psychosis experienced a transdiagnostic cognitive therapy called method of levels (MOL). Semistructured interviews were conducted with 12 individuals who were participants of a feasibility randomized controlled trial of MOL for first‐episode psychosis. Interviews were analysed using thematic analysis. Four superordinate themes were identified: 'The therapist's approach'; 'I was in control'; 'Thinking and talking'; and 'Looking at problems from a different perspective'. Our findings suggest that therapy was experienced as most helpful when participants perceived themselves to have control over the process of therapy, could explore and express a wide range of difficulties, and were able to generate new perspectives on their problems. MOL and its associated system of client‐led appointment scheduling were predominantly perceived to be helpful and appear suitable for further testing in a larger clinical trial.